Innovativeness, market intelligence practices, and firm performance of small- and medium-sized tour operators - Yap, C. S.; Cheng, Boon Liat *; Nurhuzira, M. H.; Rizal, A. (SAGE, 2018)
The study examines the effect of market intelligence practices on firm performance in the small- and medium-sized tour operators in Malaysia. Specifically, a conceptual model is developed which hypothesizes that firm innovativeness relates positively to market intelligence acquisition and market intelligence utilization which, in turn, affects firm performance. A self-administered questionnaire survey is used to garner responses from a sample of 81 tour operators. The findings indicate that firm performance is positively related to market intelligence practices both in terms of market intelligence acquisition and market intelligence utilization. In addition, it also shows that the relationship between firm innovativeness and market intelligence acquisition is stronger than the relationship between firm innovativeness and market intelligence utilization. These findings may imply that even though market intelligence practices are more prevalent among larger firms, small- and medium-sized tour operators may also benefit from having formal information processing systems and in particular in terms of acquiring and utilizing information. The limitations of the study and recommendations for future research are also discussed.